The specificity of pastoral societies in Central Asia - Szynkiewicz , Sławoj (Balcanica Posnaniensia. Acta et studia, 2007)
The author discusses complex social, economic and cultural phenomena related to the functioning of pastoral societies in Central Asia, which have shaped the history of Eurasia for centuries. The aim of the research is to show the specificity of nomadic pastoral communities in the context of their economic system, property relations, social structures, as well as relations with sedentary peoples. The starting point is the observation that this region, which is a natural migration and cultural corridor, was one of the key areas of exchange between civilisations. Based on Russian, Western and Polish literature, the author analyses various models of social and economic organisation. He critiques concepts such as „nomadic feudalism” and „oscillating states”. The conclusions indicate that pastoral societies were characterised by high adaptability and organisational flexibility, although they were limited by the extensive nature of their economy. A key element of their identity was their symbiosis with their agricultural neighbours, which led to the emergence of multicultural political organisms. The author argues that despite the stereotype of ‘nomadic plunderers’, nomads were the creators of specific forms of statehood and participants in civilisational dialogue.